The Impact of CYP3A5, CYP1A1, GSTM1, GSTT1, GSTP1 and TPMT Gene Polymorphisms on the Risk of Chronic Myeloid Leukemia: Life Sciences-Human Genetics - Kaishiv Joshi; Shruti Caplash; Dr. Satbir Kaur (International Journal of Life Science and Pharma Research, 2022)
Polymorphisms in the genes encoding drug metabolising enzymes (DME) cause inter-individual variations in metabolising exogenous and endogenous substances, which has been related to the risk of various diseases. The present study was conducted to investigate the association of CYP1A1, GSTM1, GSTT1, GSTP1 and CYP3A5 and TPMT gene polymorphisms with susceptibility to chronic myeloid leukemia (CML). 89 samples of CML patients and 135 control samples were included in this study. Genotyping of CYP1A1, GSTM1, GSTT1, GSTP1 and CYP3A5 and TPMT gene polymorphisms was performed by a Polymerase chain reaction-Restriction fragment length polymorphism (PCR-RFLP). The frequency of GSTM1 null genotype was found to be significantly higher among chronic myeloid leukemia (CML) patients vs controls (39% vs 18.5%, respectively) with a 2.85-fold increased risk for CML. The frequency of GSTT1 null was found to be significantly lower in CML patients vs controls (26% vs 40.7%). Under the dominant inheritance model, GSTP1 gene polymorphism was significantly associated with reduced risk of CML. Moreover, CYP3A5 * 6 and TPMT * 2 alleles were absent among CML patients and the control group. GSTM1 null genotype was found to be associated with an increased risk of CML whereas TPMT * 2 and CYP3A5 * 6 alleles were absent in the population of Punjab.